Laws of Desire: The Political Morality of Public Sex - Craig, Elaine (McGill Law Journal / Revue de droit de McGill)

(untitled) (McGill Law Journal / Revue de droit de McGill, 2009)
AbstractIn indecency cases, Canadian courts historically employed a model of sexual morality based on the community’s standard of tolerance. However, the Supreme Court of Canada’s recent jurisprudence addressing the role of morality in the criminal law relies upon, in order to protect, the fundamental values enshrined in the Canadian constitution. This article analyzes the Court’s decisions in R. v. Labaye and R. v. Kouri and demonstrates that these cases represent a shift in the relationship between law and sexuality. The author illuminates the possibility of a new approach by the Court to the regulation of sex. Such an approach allows for the legal recognition of pleasure behind, beyond, or outside of legal claims regarding identity, antisubordination, relationship equality, and conventional privacy rights. A new theoretical approach to the legal regulation of sexuality recognizes the importance and benefit of challenging mainstream beliefs about sexuality and subverting certain dominant sexual norms. Such an approach is firmly grounded in the principles of liberalism that Labaye reflects.